2008
DOI: 10.1021/ie800570z
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Performance of Catalysts for Catalytic Cracking by Applying a Lump-Based Kinetic Model

Abstract: In catalytic cracking, catalysts selection is not a trivial task since a catalyst should exhibit a good hydrothermal stability as well as product distributions and qualities according to the necessities of the refinery. Cracking experiments at the bench scale in a fluidized confined-bed reactor at 789 K in the catalyst to oil range of 3.0-7.5 g/g using two industrial feeds have coupled to a five-lump kinetic model for a quantitative study of a set of cracking catalysts. To a gain insight into the catalysts per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…However, with the increase of Mg/Al molar ratio diesel yield showed an upward tendency, but slurry yield showed a downward tendency. Because gasoline was typically susceptible to secondary reaction and undergoes overcracking to produce LPG [8,24], therefore, the Lewis acidity of Zn/Al 2 O 3 additive enhanced the pre-cracking of slurry to form gasoline and diesel but reduced the secondary cracking of gasoline to form LPG [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the increase of Mg/Al molar ratio diesel yield showed an upward tendency, but slurry yield showed a downward tendency. Because gasoline was typically susceptible to secondary reaction and undergoes overcracking to produce LPG [8,24], therefore, the Lewis acidity of Zn/Al 2 O 3 additive enhanced the pre-cracking of slurry to form gasoline and diesel but reduced the secondary cracking of gasoline to form LPG [25].…”
Section: Resultsmentioning
confidence: 99%
“…However, they are limited by the high capital investment and operation costs, particularly the loss of octane number of gasoline in HDS process. Catalytic technologies, named as sulfur reducing additives, have been developed and should be the most economical and easiest implement among many new approaches, such as adsorption, oxidation, and extraction reactions for refineries [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the kinetic parameters, an objective function [24] representing the difference between predicted and experimental yields for the six lumps was defined as E min a X set i¼1 X 6 j¼1 w j y exp i;j À y pre i;j 2…”
Section: Parameters Estimationmentioning
confidence: 99%
“…80 Nowadays, the global demand for FCC catalyst is ever increasing. 81 According to the report [6] for the screening and selection of FCC catalysts [15][16][17][18][19][20][21][22]. De Lasa 113 et al [19] reported their work of 8-lump kinetic modelling and 114 FCC catalyst selection using a self-designed riser simulator.…”
mentioning
confidence: 99%
“…The differential equations of the six-lump kinetic mod-313 els were solved using experimental data at 460, 480, 500 and 314 520°C by a Matlab program which was compiled according to 315 fourth order Runge-Kutta algorithm and the least square method. 316 To optimize the kinetic parameters, an objective function [22] Cat-I were obtained, respectively. As a typical operating tempera-362 ture of FCC unit, the corresponding cracking data of the two cata-363 lysts at 500°C were calculated.…”
mentioning
confidence: 99%